Casting open porous Ti foam suitable for medical applications. Issue 2 (June 2013) - Müller, Daniel Wyn; Matz, Alexander Martin; Jost, Norbert
Abstract : In the development of biocompatible synthetic materials for the surgery of bone fractures, open porous Ti foams have a high potential to find application as a geometrically and mechanically adaptable implant matrix. The present state of research mainly focuses on Ti foams produced using powder metallurgy, whereas cast manufacturing is barely investigated despite cast parts achieve higher mechanical strength and durability than those sintered. Therefore, the present study describes the manufacturing of Ti foam by precision casting using a centrifugal casting machine. Experimental investigations employed casting of CP-Ti grade 1 and grade 2 purity, and characteristics of this technique were ascertained and compared with the current proficiency in the field of dental research. The knowledge of specific influences on the feasibility of Ti foam manufacturing by precision casting – collated in this survey – enables specific optimization of the casting process as well as design enhancement relating to the cellular structure.